1992
DOI: 10.1163/156916292x00108
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors and Metaphoric Objects

Abstract: This article reports on an exploratory study that used metaphoric objects as a therapeutic aid. During Rogerian therapy sessions, a metaphoric object was handed to clients. The metaphoric object was used as a reflection of an aspect of the client's being. The clients were asked to describe the effect the object had on them. The protocols obtained were subjected to a phenomenological analysis. The study indicates that metaphoric objects can be a useful therapeutic aid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(p. 273) Indeed, the use of metaphor permeates many facets of counseling theories as evidenced in the literature. Many authors have suggested a facilitative role for metaphorical communication in counseling through stories, anecdotes, metaphorical objects, and music (e.g., Barker, 1985;Jooste & Cleaver, 1992;Saari, 1986). Metaphorical strategies have been implemented with a variety of client populations, from children to adults, as well as across a wide range of presenting concerns (cf.…”
Section: Metaphor and Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…(p. 273) Indeed, the use of metaphor permeates many facets of counseling theories as evidenced in the literature. Many authors have suggested a facilitative role for metaphorical communication in counseling through stories, anecdotes, metaphorical objects, and music (e.g., Barker, 1985;Jooste & Cleaver, 1992;Saari, 1986). Metaphorical strategies have been implemented with a variety of client populations, from children to adults, as well as across a wide range of presenting concerns (cf.…”
Section: Metaphor and Counselingmentioning
confidence: 99%
“…Thus, metaphorical communication may allow clients to explore what is "them" by talking about what is "not them." In other words, metaphors may function as a safe mediator between what is and is not currently threatening to the client (Billings, 1991;Fox, 1989;Jooste & Cleaver, 1992). Caruth and Ekstein (1966) referred to metaphor as the client's alibi, "a conscious allusion which is a way of implying what he wants to communicate without actually committing himself, a way of simultaneously keeping and revealing a secret" (p. 38).…”
Section: Working With Client Resistancementioning
confidence: 99%